The Simplification of Tax Regulations as a Strategic Approach to Mitigating Taxpayer Resistance - Hendro Prabowo (Veteran Law Review, 2026)
This study examines the increasing complexity of Indonesian tax regulations as a contributing factor to taxpayer resistance and analyzes regulatory simplification as a strategic legal solution. Tax resistance, manifested in both passive and active forms, arises from ambiguous norms, frequent legislative amendments, intricate administrative procedures, and inconsistent interpretation by tax authorities. Such complexity not only undermines legal certainty and fairness but also creates opportunities for tax avoidance and tax evasion, including practices such as transfer pricing, thin capitalization, treaty shopping, and other aggressive tax planning strategies. This research employs normative legal methodology using statutory and conceptual approaches, relying on legislative analysis and relevant doctrinal literature. The findings indicate that excessive regulatory fragmentation and procedural burdens weaken voluntary compliance and erode public trust. Simplification—through clearer codification, harmonization of tax laws, transparent procedures, and strengthened legal certainty—can enhance horizontal and vertical equity, improve accessibility of tax norms, and reduce incentives for resistance. Therefore, regulatory simplification constitutes a structural reform strategy to reinforce taxpayer compliance and ensure sustainable state revenue.